PENGUJIAN FINANCIAL STATEMENT FRAUD MENGGUNAKAN FRAUD DIAMOND (Media Riset Akuntansi, 2022)
This study aims to examine the effect of diamond fraud with financial stability proxies, financial targets, ineffective monitoring, total assets accruals and change in directors on financial statement fraud. The sampling technique used was purposive sampling method and based on this method, a sample size of 114 was obtained from Infrastructure, Utilities, and Transportation Sector Companies listed on the Indonesia Stock Exchange for the 2015-2018 period. The data analysis method used is multiple linear regression analysis. The results of the study prove that financial stability has a negative effect on financial statement fraud, financial targets have a positive effect on financial statement fraud, ineffective monitoring has a positive effect on financial statement fraud, total assets accruals have no effect on financial statement fraud, and change in director has no effect on financial statements. fraud